2020
DOI: 10.5210/spir.v2020i0.11180
|View full text |Cite
|
Sign up to set email alerts
|

"Good Social Media?": Underrepresented Youth Perspectives on the Ethical and Equitable Design of Social Media Platforms

Abstract: This study investigates underrepresented youths’ perspectives on social media design and how these may inform the development of more ethical and equitable social media apps. In contrast to the tradition of universal design in the field of human-computer interaction, this research centers difference to investigate how users’ perspectives and expectations, shaped by their identities, help determine the affordances of social media and their ethical implications. Twenty-five in-depth interviews and youth-guided “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Social media platforms are not inherently or exclusively bad for users' autonomy. On the contrary, social media platforms have been experienced as empowering spaces that allow individuals to express themselves and organize for political resistance (Brough, Literat, and Ikin 2020;Williams 2015). Hence, in our view, technology-mediated social interactions require new legal frameworks, new business models, and, most tangibly, new designs in order to avoid the stated problems.…”
Section: Problems With Existing Social Media Platformsmentioning
confidence: 99%
See 2 more Smart Citations
“…Social media platforms are not inherently or exclusively bad for users' autonomy. On the contrary, social media platforms have been experienced as empowering spaces that allow individuals to express themselves and organize for political resistance (Brough, Literat, and Ikin 2020;Williams 2015). Hence, in our view, technology-mediated social interactions require new legal frameworks, new business models, and, most tangibly, new designs in order to avoid the stated problems.…”
Section: Problems With Existing Social Media Platformsmentioning
confidence: 99%
“…The lack of diversity in a platform has implications for users. Brough, Literat, and Ikin (2020) found that youth felt the need to conform to standard community norms to be seen and recognized in social media platforms. Being different or posting about less covered topics is not rewarded by the system.…”
Section: Problems With Existing Social Media Platformsmentioning
confidence: 99%
See 1 more Smart Citation
“…SM enabled the youth in the formation of identity-based communities and networks. An example is Brough et al (2020) unveils shared success stories among low-income and under-resourced youth of getting work, connecting with professional contacts, or gaining access to career mentorship due to interactions on SM.…”
Section: Youth Perceptions and Use Of Smmentioning
confidence: 99%
“…Possible and idealized selves can be presented online and this can propagate pressure to continually adopt this fictitious persona (Burnette et al, 2017). Allowing others to “like” and comment on personal lives can have implications for self-esteem; how they are perceived by others is inextricably linked to how they feel about themselves and this social acceptance and approval by peers is essential for the wellbeing of children and young people (Brough et al, 2020; Chae, 2017; Koutamantis et al, 2015).…”
Section: Introductionmentioning
confidence: 99%